Comparison of adjuvants to optimize influenza neutralizing antibody responses. Issue 42 (30th September 2019) - Rudicell, Rebecca S.; Garinot, Marie; Kanekiyo, Masaru; Kamp, Heather D.; Swanson, Kurt; Chou, Te-hui; Dai, Shujia; Bedel, Olivier; Simard, Daniel; Gillespie, Rebecca A.; Yang, Kanwen; Reardon, Michael; et al.
Abstract: Seasonal influenza vaccines represent a positive intervention to limit the spread of the virus and protect public health. Yet continual influenza evolution and its ability to evade immunity pose a constant threat. For these reasons, vaccines with improved potency and breadth of protection remain an important need. We previously developed a next-generation influenza vaccine that displays the trimeric influenza hemagglutinin (HA) on a ferritin nanoparticle (NP) to optimize its presentation. Similar to other vaccines, HA-nanoparticle vaccine efficacy is increased by the inclusion of adjuvants during immunization. To identify the optimal adjuvants to enhance influenza immunity, we systematically analyzed TLR agonists for their ability to elicit immune responses. HA-NPs were compatible with nearly all adjuvants tested, including TLR2, TLR4, TLR7/8, and TLR9 agonists, squalene oil-in-water mixtures, and STING agonists. In addition, we chemically conjugated TLR7/8 and TLR9 ligands directly to the HA-ferritin nanoparticle. These TLR agonist-conjugated nanoparticles induced stronger antibody responses than nanoparticles alone, which allowed the use of a 5000-fold-lower dose of adjuvant than traditional admixtures. One candidate, the oil-in-water adjuvant AF03, was also tested in non-human primates and showed strong induction of neutralizing responses against both matched and heterologous H1N1 viruses. These data suggest that AF03, along with certain TLR agonists, enhance strong neutralizing antibody responses following influenza vaccination and may improve the breadth, potency, and ultimately vaccine protection in humans.